Examination of the influence of boron on the microstructure and properties of low C ferritic steels using NanoSIMS and TEM - Ahmed, S; Titchmarsh, J; Kilburn, MR; Grovenor, C (2006)
In order to understand the influence of boron on the grain size and microstructure of a series of low carbon steel rods the imaging of elemental distributions of B, N and C has been undertaken using Cameca NanoSIMS 50. This instrument provides the high sensitivity, spatial and mass resolution required for the identification of small precipitates and segregation of light elements that are traditionally difficult to study by other micro-analytical techniques. However, the use of NanoSIMS to investigate metallurgical problems is complicated by matrix effects. This leads to changes in ionization yield and variable sputter rates due to the matrix composition. In order to help overcome this problem, the results from the sequential characterisation of exactly the same area of a sample using first transmission electron microscopy (TEM) and then NanoSIMS will be described. This permits the direct comparison of sensitivity and spatial resolution on precisely the same individual particles, which can help us determine the most efficient characterisation strategy. (c) 2006 Elsevier B.V. All rights reserved.